Cell mechanics: When tissues collide - Schwarz, Ulrich S.; Ziebert, Falko (Nature materials, 2017)
Quantitative analysis of colliding cell monolayers reveals surprising wave phenomena involving contractility, jamming and activation of epithelial cells.